Supergods what masked vigilantes, miraculous mutants, and a sun god from Smallville can teach us about being human - Morrison, Grant (Spiegel & Grau, 2011)
Morrison draws on history, art, mythology, and his own astonishing journeys through this alternate universe as a comic book writer to provide the first true chronicle of the superhero.